Well Performance Analysis based on Pumping Test - Fairur Affandy, Afzatul Ainisha; Musa, Sabariah (Recent Trends in Civil Engineering and Built Environment, 2024)
Water is a renewable resource that is perpetually replenished. The necessity of water for the existence of all species, including humans, is well acknowledged. A number of the countries that make up Malaysia suffered from water shortages a few years ago, which almost certainly led to the implementation of predetermined water limitations. In light of the concerns raised, this study objective is to identify the characteristics of the groundwater obtain at RECESS, UTHM and to evaluate the well performance acquired from the groundwater pumping activities. The procedure is carried out as a single well pumping test, and as part of the data gathering process, a constant rate pumping test method is utilised as the analytical tool. Five characteristics of groundwater were analysed; transmissivity (T), storativity (S), hydraulic conductivity (K), flow rate (Q) and specific yield (Sy) gathered from the pumping test activities. A recharge well (REWES) is a device used to regulate the amount of water pumped into a groundwater reservoir. The result from this study are the Q = 59.46  , T = 3.628  S = 0.027, K = 0.087, and lastly  = 0.971 for sample 1. The feasibility of the well was evaluated based on its parameters and quantity of groundwater and for the result for the well performance, the performance of flow rate of well was increasing by 27 %. The well's water supply is still sufficient, but the water level and volume have declined. Although smaller, the well can nevertheless provide water over the long term. If the well is not pumped excessively, it can be utilised for over a decade longer.